2021
DOI: 10.3390/atmos12060792
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on the Hydrometeorological Characteristics of the Soan River Basin, Pakistan

Abstract: The global hydrological cycle is vulnerable to changing climatic conditions, especially in developing regions, which lack abundant resources and management of freshwater resources. This study evaluates the impacts of climate change on the hydrological regime of the Chirah and Dhoke Pathan sub catchments of the Soan River Basin (SRB), in Pakistan, by using the climate models included in the NEX-GDDP dataset and the hydrological model HBV-light. After proper calibration and validation, the latter is forced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The HBV model [25,26] is a conceptual, semi-distributed hydrological model and HBVlight (version 4.0.0.24) is the version developed by Seibert and Vis [27]. It is a widely used model and its performance has been evaluated in many climatically diverse catchments around the globe [28][29][30][31]. The HBV-light was used in this study to simulate daily streamflow for each catchment.…”
Section: Description Of Observed Data Pps and The Hydrological Modelmentioning
confidence: 99%
“…The HBV model [25,26] is a conceptual, semi-distributed hydrological model and HBVlight (version 4.0.0.24) is the version developed by Seibert and Vis [27]. It is a widely used model and its performance has been evaluated in many climatically diverse catchments around the globe [28][29][30][31]. The HBV-light was used in this study to simulate daily streamflow for each catchment.…”
Section: Description Of Observed Data Pps and The Hydrological Modelmentioning
confidence: 99%
“…assessed the effects of climate change on streamflow and found a 10%-15% increase in the mean annual flow in the transboundary Jhelum River Basin of Pakistan and India. Usman et al (2021) assessed the impacts of climate change on streamflow under various RCP scenarios, and Shahid et al (2018) found that streamflow will decrease in the Soan River Basin, Pakistan. Anjum et al (2019) found that climate change will enhance the annual average flow under various RCP scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Mann-Kendall trend test was used to analyse the changing trend of ET 0 , ET a and P e . Usman et al 2021 [5] used surface energy balance system model to estimate Ea and FAO-56 Penman-Monteith method to estimate ET 0 and comparison between them.…”
Section: Introductionmentioning
confidence: 99%